Social justice leadership and inclusion: a genealogy. (1st October 2016) - Lewis, Katherine
ABSTRACT: The purpose of this article is to engage in an historical analysis of research about two concepts: social justice leadership and leadership for inclusion. Recent experiences have caused me to wonder about our interpretations of justice, equity, and inclusion. Analysis of the relevant literature revealed a lack of consensus among scholars as to a clear, operational definition of both social justice leadership and inclusion. I use a Foucauldian genealogical method to examine texts and uncover the historical development of social justice leadership and leadership for inclusion in the United States. Uncovering past meanings and contexts should help illuminate current meanings and uses of these concepts. It is recommended that leaders engage in critical reflection to uncover the common sense language of equity-oriented leadership practices and that researchers take a more critical, historical, open stance of social justice leadership, and inclusion.